THE POLITENESS STRATEGIES USED BY STUDENT OF ENGLISH STUDY PROGRAM IN UNIVERSITAS ISLAM LAMONGAN - Widyaiswara, Tiara; Faridah, Fita; Luthfiyati, Dian (Faculty of Teacher Training and Education, English Department, UNISKA, Kediri, 2023)
This study aims to analyze the politeness strategies used by English Study Program student. The student is first semester in study process. In completing this research, the researcher used a qualitative descriptive method and the theory of Brown and Levinson. From this study, the researcher found four kinds of politeness strategies used by the English Study Program student, those are bald on record, positive politeness, negative politeness and Off-record. The factors influence the politeness strategy used by the main ss are the payoffs and social variables. Furthermore, sociological variables also affect the use of politeness strategies used by students, which are social distance, relative power and rank of imposition.